Espaço e técnica nas Sertanias do Triângulo Mineiro: uma geoliteratura do mundo rural. - Brito, Adriana Lacerda de (2017)
This work aims to understand the relations between the space and the techniques in the geoliterature in the rural world of Sertão da FarinhaPodre. To do so, we are going to use the Sertão da FarinhaPodre works: the historic romance IPIACUPA (2013) by Ernesto Rosa, and the book NosConfins do Sertão da FarinhaPodre by Mario Lara (2009). The themes approached are dear to the philosophy of science, so we resorted to the contemporary literature to interpret the relations between society and naturepictured in the literary works analyzed. The rural world constituted where it was once “sertão” emerges slowly from the advances related to modernity, guided by the technical mediation that appears in the constitutions of territory and landscape that constitute the present geographic space. In the experience lived by the authors and readers, we found contexts of the narrative’s general outline where the worldimages about the passage through Sertão da FarinhaPodre are also pictured. Thus, representations of the rural world surround the space of the works analyzed, contributing to liberating interpretations as not only the limits of techniques, but also the advances of a whole society are recognized.